Natural ventilation in reduction of indoor radon concentration in high background radiation area dwellings Ramsar, Iran - Nasab, Lotf Ali Mehdipour (2013)
Recent studies show that radon inhalation even at low concentrations poses a risk of developing lung cancer. Additionally, there are reports representing that natural radon exposure may be a risk factor for squamous cell carcinoma or chronic obstructive pulmonary disease mortality. It has been reported that the radon health risk is proportional to its concentration down to the Environmental Protection Agency of US’s action level of 148Bq/m3. Although naturally occurring isotopes of radon in indoor air are identified as the second leading cause of lung cancer after tobacco smoking, there is limited consequenceof data on the incidence of radon-related lung cancers in Iran.Ramsar, a northern coastal city of Iran, has some areas with the highest levels of natural radiation background to date. They are considered the high level natural radiation areas (HLNRAs) of Ramsar, in particular in Talesh-Mahalleh district, in which the effective dose equivalent is a few times higher than the International Commission on Radiological Protection (ICRP)recommended radiation dose limits for radiation workers. According to U.S. Environmental Protection Agency (EPA) estimation, Radon is the first leading cause of lung cancer among non-smokers. In addition, direct and indirect radon-induced lung cancer health care has cost the USA over 2 billion dollars annually. Although radon reduction systems including architectural considerations can reduce the radon levels in buildings by up to 99 percent, architectures are often unaware of the risk of radon inhalation and how to reduce the radon levels. Furthermore, radon exposure and consequent of health effect are not part of building regulation in Iran to be considered into the building construction, construction materials and building utilization by regulatory authorities.In this study after reviewing the meteorological data of Ramsar during 1955-2005, the soil sampling was done in the radon prone area of Ramsar at four levels of activities classified as extremely hot, severely hot, very hot, and hot. The samples were placed in a model house one after another and the radon concentrations were measured with and without intervention conditions using a Prassi portable radon gas survey meter.For the extremely hot soil samples, the mean radon concentrations measured for 24 h inside the model house was about 1615 Bq/m3 when all windows were closed. When the windows were opened in the wind direction the radon level decreased to 89 Bq/m3(96% reduction)and when the windows were opened in the opposite of wind direction the radon level decreased to 139Bq/m3 (91% reduction). Interestingly, when crossed windows were opened for the same 24 h duration, the radon level was about 144 Bq/m3(91%). For simulation of cold seasons, when all windows were usually closed, the chimney effect reduced the radon level to around 323Bq/m3(80%). For the other severely hot, very hot and hot soil samples, the natural ventilation interventions effectively reduced the radon concentration in proportion with their radon concentration.The annual equivalent dose of man and the annual effective dose of human lung associated with the radon intake in radon prone areas of Ramsar were also studied before and after ventilation interventions. For extremely hot soil samples, the mean annual equivalent dose and the annual effective dose inside the model house before intervention or when windows closed were about 925 and 111 mSvy-1respectively. When windowswere opened in the wind direction, the annual equivalent dose of man and the annual effective dose of human lung decreased to 20.50 and 2.46 mSv y-1, respectively. When windows were opened in opposite of the wind direction the annual equivalent dose of man and the annual effective dose of human lung decreased to 34.70 and 4.16mSv y-1respectively. When crossed windows were opened in silent condition(no wind), these two values were reduced to 45.33 and 5.43mSv y-1respectively. For the other severely hot, very hot and hot soil samples, the natural ventilation interventions effectively reduced the annual equivalent dose of man as well as the annual effective dose of human lung accordingly. The results of the natural ventilation of HLNRAs show that these simple cost-effective interventions can significantly reduce the radon concentration, the annual equivalent dose of man, and the annual effective dose of human lung to about of 90% of their initial values.These techniques are highly recommended to be used by residents and inhabitants of radon prone areas of Ramsar.